A Spanish outlook: media messages and refugees from Eastern Europe - Eiroa San Francisco, Matilde (Estudios sobre el Mensaje Periodístico, 2012)
This text aims to analyze the messages and the mass media produced by refugees from the Iron Curtain and Spanish institutions. These media are a unique chapter in the Spanish communication, which is understood from the existing correlation between national information production and the international, because the spread along several countries, mainly in Europe and United States. In the article we study the content and we wonder what kind of functions had, which connection had with another anticommunist Diaspora media and the role played between this collective.
Keywords: anticommunist newspaper; political refugees; Eastern Europe; Francoism.